Functional consequences of novel IgG3 allelic variation CAP256-VRC26.25 - Khan, Fonguh Oliver (University of the Witwatersrand, Johannesburg, 2024)
Broadly neutralizing antibodies (bNAbs) isolated from HIV-1 individuals have shown promise in prevention. We have previously demonstrated that the IgG3 isotype significantly improved the neutralization potency of CAP256-VRC26.25 over the routinely used IgG1 constant region. However, there is significant allelic diversity in immunoglobulin constant heavy G chain 3 (IGHG3), especially in African populations, of which the functional relevance is unknown compared to IgG1 version. This study assessed whether allelic variation in IgG3 could further improve neutralization potency. CAP256-VRC26.25 bNAb was engineered and expressed as 12 different IgG3 allelic variants, including two novel variants, as determined from previous IGHG3 sequencing data from the CAPRISA 002 cohort. These were tested for neutralization against an eight- virus panel and compared to the IgG1 version. Overall, the IgG3 versions of CAP256-VRC26.25 showed improved neutralization compared to the IgG1 version. Further, there were significant differences between allelic variants, IgG3*01 versus IgG3*04 (p=0.0038), IgG3*01 versus IgG3*15 (p=0.0013), IgG3*13 versus IgG3*04 (p=0.01570) and IgG3*13 versus IgG3*15 (p=0.0059). IgG3*01 showed the highest fold change (median value 8.0) relative to IgG1. IgG3*04 and IgG3*15 showed the least fold change (median value 2.2). This is due to the short hinge length of IgG3*04 and amino acid differences in IgG3*15. IgG3*01 and IgG3*13 were the most potent variants. This confirms the importance of the constant region in neutralization which has been supported by previous studies. Thus, hinge length and amino acid differences in the constant region impact neutralization. This study shows that allelic variation in the constant region can impact on neutralizationpotency and supports leveraging genetic diversity to improve antibody function
A Dissertation submitted in partial fulfillment of the requirements for the degree of Master of Science (Med) in Vaccinology. to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg,Johannesburg, 2024
Keywords: Immunoglobulin G 3 (IgG3); Allelic variants; Broady Neutralizing Antibodies (bNAbs); Neutralization; Fold change differences; UCTD; SDG-3: Good health and well-being